Mapping of chromosomal regions influencing immunological responses to gastrointestinal nematode infections in mice - Menge, D.M.; Behnke, J.M.; Lowe, A.; Gibson, John P.; Iraqi, F.A.; Baker, R.L.; Wakelin, D. (Wiley, 2003)
This paper reports the results of a genome-wide search for quantitative trait loci (QTL) influencing immunological responses to infection with the gastro-intestinal nematode parasite Heligmosomoides polygyrus in an F2 population created by crossing the resistant SWR and the susceptible CBA inbred mouse strains. Following infections, intestinal granuloma score at post mortem, mucosal mast cell protease 1, and IgE and IgG1 titres were recorded. The susceptible CBA mice had significantly higher IgG1, but significantly lower IgE, mucosal mast cell protease 1 and granuloma scores than SWR mice. Significant QTL were mapped to chromosomes 4, 11, 13 and 17 for granuloma score; chromosomes 12 and 17 for IgE; chromosome 10, 17 and 18 for IgG1 and chromosomes 1, 9, 10, 11, 17 and 18 for mucosal mast cell protease 1. Chromosomes 10, 11, 17 and 18 had QTL affecting more than one trait, and these are most likely to represent single QTL with multiple effects rather than multiple QTL. Some of these QTL map to regions known to harbour genes responsible for the induction of immunological responses to intestinal worms.